A rare presentation of palmoplantar lichen planus - G. N. Mikheyev; T. V. Krasnoselskikh; V. V. Yastrebov; A. E. Grigorian (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Lichen planus is a disease characterized by a large variety of clinical forms and morphological patterns. Localized rash on the palms and soles is considered rare and may create certain problems in diagnosis if it is present as an isolated finding in the absence of typical papular rash on the skin and mucous membranes, and such problems may be solved by histological examination. We report a case of a 41-year-old male with palmoplantar lichen planus. The disease was characterized by pruritic erythematous well-defined plaques dotted wit h multiple, punctate brown keratotic plugs on the palms and soles, which were difficult to separate when scraping. Histological examination revealed changes in the excretory ducts of eccrine sweat glands. We suggest that the presented case is a unique clinicopathologic variant of palmoplantar lichen planus that may be designated by the term "lichen planoporitis."